ANALISIS PERBANDINGAN PENGARUH LOKASI USAHA TERHADAP PENJUALAN PADA PASAR KELAPA DUA DAN PASAR THUMBURUNI FAKFAK - Deisya Maulida Al Hamid; Nelson Rumui; Siti Kurnia; Wa Mutia (LP2M Universitas Bina Bangsa, 2022)
This study aims to determine how influential the business location factor on sales in determining the selection of the right market location in Fakfak Regency and to compare the effect of business location at Thumburuni Market and Kelapa Dua Market on sales volume in Fakfak Regency. The population in this study was 50% of the number of traders in the coconut market, with a sample of 70 traders. The data collected in the form of primary data (questionnaires) and secondary (literature studies, both books, journals, and similar research) so as to strengthen this research. The data analysis method in this study used simple linear regression analysis. And from the results of testing using SPSS, the Anova table obtained an F number of 30,518 with a significance level (probability number) of 0.000. Because the number 0.000 <0.05, the regression model is feasible to use to predict the effect of business location on sales. It is known that the coefficient of determination (R Square) is 0.310. This means that the contribution of the influence of location to sales volume is 31%, while the remaining 69% is influenced by other variables, namely variables that are not included in this model. So, it can be said that the influence of the business location variable on sales volume is quite significant